Analisis Penerapan Prinsip-Prinsip Pemasyarakatan pada Pembinaan di Lembaga Pemasyarakatan Perempuan: (Studi pada Lapas Perempuan II A Bandar Lampung) - Haery Fajri; Diah Gustiniati; Malicia Evendia (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The implementation of the training of prisoners on the basis of the system of socialization aims to ensure that the prisoner becomes a good citizen of society, obeying the law, upholding moral, social and religious values, so as to a safe, orderly and peaceful life of the community in accordance with the Law No. 22 Year 2022 on Socialization. How is the application of the principles of women's marketing in construction at the Women's Marketing Institute of Class IIA in Bandar Lampung, how is the obstacle to the application in the Women ' s Marketing Institution of Class IIIA and how is it possible to overcome the obstacles to the implementation of the principle of women’s Marketing in construction in the women' s marketing institutions of Class IA in bandar Lampung? Data analysis using qualitative data analysis. The implementation of the principles of establishment on the construction of the Women's Marketing Institute of the IIA Class of Bandar Lampung refers to the existing procedures and has been implemented in accordance with the procedures existing, implemented the principle of establishing after passing through four stages, namely the orientation stage, the assimilation stage for the prisoners who have run less than 1/3 of the criminal period, the asimilation level for the inmates who have passed less than 1⁄2 of the penal period as well as the stage of integration with the community environment. The way to overcome the obstacles to the implementation of the principles of promotion in the construction of the Women's Marketing Institute of Class IIA in Bandar Lampung is by submitting the formation of additional female employees, maximizing the function of the female citizens' bloc officers, improving the quality of the staff or officers and adding the means and facilities in the building of women's citizens.